Innovation in Teaching and Learning Education in the Digital Era - Afrida Yanis (Global Perspectives in Education Journal, 2025)
As human needs become more complex, educational technology is not only using tools (machines) for learning in the current era of information technology. Innovative teachers can create a learning environment that motivates students, increases creativity, and stimulates their interest in learning. This study aims to determine the description of innovation in teaching and learning education in the digital era. The research method used is the Library Research Method. The data that has been collected is triangulated and reduced to produce conclusions. Education, especially State Senior High School 1, Pasir Penyu District, Indragiri Hulu Regency, is one of the instruments affected by the reform movement with four students as subjects. Researchers found several important aspects regarding teaching and learning in the digital era, namely, learning in the digital era has different characteristics from student learning in the past; the generation in this era are those with digital native characters. Students today are born, grow, and grow up in direct contact with the digital world, so the information obtained will be different from previous students. Innovation in teaching and learning is a discovery that can be an idea, item, event, or method observed as something new for the world of education, such as using media in the learning process and utilizing smartphones for learning. Other media that can help students learn well, media here is an innovation. Teachers, as partners in learning, must be able to design learning activities so that students obtain more information than the time provided.